2014
DOI: 10.4017/gt.2014.12.3.008.00
|View full text |Cite
|
Sign up to set email alerts
|

Gaming preferences of aging generations

Abstract: Increasing evidence suggests that action digital game training can improve a variety of perceptual and cognitive abilities, including those that decline most with age. Unfortunately, previous work has found that older adults dislike these games and adherence may be poor for action game-based interventions. The focus of the current study was to better understand the types of games older adults are willing to play and explore predictors of game preference (e.g., gender, age, technology experience, personality). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 41 publications
6
29
0
3
Order By: Relevance
“…To date, most video game training studies have used hardcore action video games (especially first-person shooter [FPS]) to demonstrate how video games can improve perceptual and cognitive abilities, notably those that are also subject to age-associated decline [4,5]. Although action video games are mainly targeted at younger audiences, these kinds of games present barriers to older adults.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, most video game training studies have used hardcore action video games (especially first-person shooter [FPS]) to demonstrate how video games can improve perceptual and cognitive abilities, notably those that are also subject to age-associated decline [4,5]. Although action video games are mainly targeted at younger audiences, these kinds of games present barriers to older adults.…”
Section: Introductionmentioning
confidence: 99%
“…First, learning to play and interact with fast-paced action video games can be very difficult and demotivating for older adults. Second, questionnaire and playtest studies have found that older adults generally dislike action video games, especially when featuring violent content [4,6-8]. Together, this leads to a situation where older adults, despite promising cognitive benefits, are less willing and motivated to play action video games, and thus less likely to follow through with action video game interventions [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations